PENGARUH MANAJEMAN STRATEGIK, KEPEMIMPINAN DANLINGKUNGAN KERJA TERHADAP PERFORMA KARYAWANPT PLN UNIT X - Afrianda, Rio; Yosepha, Sri Yanthy (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2025)
Strategic management and leadership have a significant influence on employeeperformance at PT PLN unit X, with a t-count value of 3.762, which is greater than the ttable of 1.699 (t count > t table) and a significance value of less than 0.05 (0.001 < 0.05).This shows that strategic management contributes significantly to employeeperformance. In addition, the work environment is also proven to have a significant effecton employee performance, with a t-count value of 2.986 which is greater than the t tableof 1.699 (t count > t table) and a significance value of less than 0.05 (0.006 < 0.05). Theresults of the simultaneous test show that the F count value is 39.192, higher than the Ftable of 2.960 (F count > F table) with a significance level of less than 0.05 (0.000 <0.05). Therefore, the proposed research hypothesis can be accepted because it isproven to be true.